2021
DOI: 10.2147/cmar.s292048
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-to-Monocyte Ratio is Associated with the Poor Prognosis of Breast Cancer Patients Receiving Neoadjuvant Chemotherapy

Abstract: Purpose Systemic inflammatory cell ratio, neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), and lymphocyte–monocyte ratio (LMR) are used as prognostic indicators for several types of tumors. The purpose of this study was to evaluate the predictive value of inflammatory markers for pathological response and prognosis in breast cancer patients receiving neoadjuvant chemotherapy (NAC). Methods In this study, we collected data of 203 breast cancer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 39 publications
3
34
1
Order By: Relevance
“…Concerning LMR, it was associated with poor OS in a meta-analysis of patients with solid tumors [42]. In the BC neoadjuvant chemotherapy setting, a recent study con rmed this result in a multivariable analysis and showed that patients with low LMR had shorter DFS [43].…”
Section: Discussionmentioning
confidence: 89%
“…Concerning LMR, it was associated with poor OS in a meta-analysis of patients with solid tumors [42]. In the BC neoadjuvant chemotherapy setting, a recent study con rmed this result in a multivariable analysis and showed that patients with low LMR had shorter DFS [43].…”
Section: Discussionmentioning
confidence: 89%
“…We have collected baseline counts of neutrophil-lymphocyte and monocytes and platelets for peripheral blood parameters to calculate our inflammatory indices (NLR, LMR, and PLR). Cut-off points for NLR, LMR, and PLR were obtained from a similar study that documented the optimal ratio of 3%, 6.2%, 135%, respectively (Ma et al, 2021). For RDW, we have used a range from a focused study on breast cancer (11-14.1) (Seretis et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15] In terms of breast cancer, several studies have shown that inflammatory-nutritional indexes, including the platelet-lymphocyte ratio (PLR), systemic inflammation score (SIS), neutrophil-lymphocyte ratio (NLR), monocyte-lymphocyte ratio (MLR), Controlling Nutritional Status (CONUT), and systemic immune-inflammation index (SII), are markedly associated with survival outcomes. [16][17][18][19][20][21] Qi et al first recognized the system inflammation response index (SIRI) as a predictor for pancreatic cancer. The prognostic value of this index in patients with breast cancer was also explored in our previous study.…”
Section: Introductionmentioning
confidence: 99%